Analysis of H2/Air Polarization Losses of Low-Platinum-Loading Cathodes with Various I/C Ratios and Carbon Supports. Issue 15 (1st January 2018) - Yu, Haoran; Bonville, Leonard; Maric, Radenka
Abstract : Reduction of platinum loading is one of the major challenges for the commercialization of proton exchange membrane fuel cells. The role of catalyst layer microstructure and ionomer content is critically important at ultra-low platinum loading due to enhanced oxygen transport resistance compared to high platinum loading. In the present work, catalyst-coated membranes with two types of carbon supports and various I/C ratios are fabricated using reactive spray deposition technology (RSDT) where low Pt loading (cathode 0.1 mg cm −2, anode 0.05 mg cm −2 ) catalyst layers are directly deposited on Nafion membranes. Similar performance is obtained at optimal I/C ratios for Pt/Ketjen Black (KB) CCMs and Pt /multi-wall carbon nanotube (MWNT) CCMs, with optimal I/C ratio being 1.0 and 0.5, respectively. Six types of polarization overpotentials are analyzed using a six-step method established in our previous work to elucidate the influence of catalyst layer microstructure and ionomer content on fuel cell performance. Since MWNT requires 50% less ionomer and are chemically more stable than KB, MWNT is a preferred support for ultra-low platinum loading electrodes. The six-step method connects catalyst layer properties with specifically targeted overpotentials and is thus a powerful tool in catalyst layer optimization.